2014
DOI: 10.1093/mnras/stu1297
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast outflows in radio-loud active galactic nuclei

Abstract: Recent X-ray observations show absorbing winds with velocities up to mildlyrelativistic values of the order of ∼0.1c in a limited sample of 6 broad-line radio galaxies. They are observed as blue-shifted Fe XXV-XXVI K-shell absorption lines, similarly to the ultra-fast outflows (UFOs) reported in Seyferts and quasars. In this work we extend the search for such Fe K absorption lines to a larger sample of 26 radio-loud AGNs observed with XMM-Newton and Suzaku. The sample is drawn from the Swift BAT 58-month catal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
133
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(151 citation statements)
references
References 118 publications
(163 reference statements)
18
133
0
Order By: Relevance
“…Similar absorption lines have recently been discovered in the NuSTAR spectrum of CygA, a bright FRII galaxy (Reynolds et al 2015). When adding Gaussian absorption lines to our data of CenA, with the energies fixed at the values found by Tombesi et al (2014) and the width set to 1 eV, we find a marginal improvement of 7 2 c D = for two additional parameters. However, if we allow the energies to vary, the fit does not converge.…”
Section: CMsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar absorption lines have recently been discovered in the NuSTAR spectrum of CygA, a bright FRII galaxy (Reynolds et al 2015). When adding Gaussian absorption lines to our data of CenA, with the energies fixed at the values found by Tombesi et al (2014) and the width set to 1 eV, we find a marginal improvement of 7 2 c D = for two additional parameters. However, if we allow the energies to vary, the fit does not converge.…”
Section: CMsupporting
confidence: 83%
“…Using Suzaku data, Tombesi et al (2014) found evidence for two weak absorption lines at 6.66 and 6.95 keV, which they interpreted as evidence for a slow wind. Similar absorption lines have recently been discovered in the NuSTAR spectrum of CygA, a bright FRII galaxy (Reynolds et al 2015).…”
Section: CMmentioning
confidence: 99%
“…3.2). As discussed by Tombesi et al (2014), where a minimum wind covering fraction of C ≈ (0.3−0.7) was derived, UFOs in radio-loud AGN are likely to be covering a significant portion of the sky as seen by the central source. Since derived statistically for a sample of 26 radio-loud AGN (using also the information from the radio jet inclination angle to visualize the geometry of the system, assuming that the jet is perpendicular to the accretion disk), this result implies that the absorbing material is not highly collimated as expected in the case of jets; as a result, an accretion-disk wind is favored.…”
Section: Radio Datamentioning
confidence: 87%
“…At the end of this obscured phase, massive quasar-driven outflows blow away most of the cold gas reservoir, creating a population of "red-and-dead" gas-poor elliptical galaxies (e.g., Cattaneo et al 2009). Support for this picture -at least for the most luminous AGN -comes from observations of kpc-scale outflows of molecular gas (e.g., Feruglio et al 2010;Sturm et al 2011;Veilleux et al 2013;Cicone et al 2014), as well as of neutral and ionized gas (e.g., Nesvadba et al 2008;Alexander et aloutflows (UFOs, with velocities typically up to 0.1-0.4c) have been clearly detected in X-rays in a sizable sample of AGN at low redshift (e.g., Reeves et al 2003;Pounds et al 2003;Tombesi et al 2010Tombesi et al , 2012aTombesi et al , 2014Tombesi et al , 2015Giustini et al 2011;Patrick et al 2012;Gofford et al 2013Gofford et al , 2015King et al 2014;Nardini et al 2015;Ballo et al 2015; see also Cappi 2006 for an early review; and Fabian 2012 for a more recent one) and also in a limited number of high-redshift quasars (e.g., Chartas et al 2002Chartas et al , 2007Chartas et al , 2009Chartas et al , 2014Saez et al 2009;Lanzuisi et al 2012). Although original claims of blueshifted absorption features were strongly debated (see Vaughan & Uttley 2008), recent high photon statistics in X-ray spectra of both radio-quiet (e.g., Tombesi et al 2010Tombesi et al , 2011Tombesi et al , 2012aGofford et al 2013) and radio-loud AGN (e.g., Gofford et al 2013;Tombesi et al 2014) have undoubtedly shown that these outflows are not ra...…”
Section: Introductionmentioning
confidence: 99%
“…The warm absorbers give rise to several narrow absorption features (from several elements over a wide range of ionization parameters), which when observed at high spectral resolution are generally blueshifted by a few hundred km s −1 up to few thousand km s −1 , implying the presence of outflowing winds. Recently, systematic studies of the X-ray spectra of bright nearby AGNs unveiled that blue-shifted absorption features due to Fe xxv and Fe xxvi are present in at least 40% of the radio-quiet AGNs (Tombesi et al 2010a; Tombesi et al 2011Tombesi et al , 2012Patrick et al 2012; Gofford et al 2013) and also in a sample of local Broad Line Radio Galaxies (Tombesi et al 2010b(Tombesi et al , 2014. Compared to the soft warm absorbers, these winds are characterized by high column densities (N H > 10 23 cm −2 ), high ionization, and high velocities (v > 0.1 c); thus, their outflow rate can be huge (several M yr −1 ) and they can play a key role in the coevolution of the massive black hole and the host galaxy.…”
Section: Introductionmentioning
confidence: 99%